Acrylic adhesive composition

JP2025024637APending Publication Date: 2025-02-20CEMEDINE CO LTD

Patent Information

Application Number
JP2023128893
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-07
Publication Date
2025-02-20

Smart Images

  • Figure 2025024637000001
    Figure 2025024637000001
Patent Text Reader

Abstract

To provide an acrylic adhesive composition containing a polytetramethylene glycol-based urethane (meth)acrylate compound as an essential component, which has low viscosity and excellent workability, and exhibits high peeling strength and shear strength.SOLUTION: An acrylic adhesive composition contains: (A) a polytetramethylene glycol-based urethane (meth)acrylate compound having a (meth)acrylate group at a terminal, which is obtained by reacting (a) a polyol compound and (b) a polyisocyanate compound in a molar ratio of the component (b) to the component (a) of 0 to 0.5 with (c) a terminated (meth)acrylating agent; (B) a polymerizable vinyl monomer; (c) an organic peroxide; and (D) a reducing agent, as essential components.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an acrylic adhesive composition, and more particularly to an acrylic adhesive composition that has a low viscosity, excellent workability, and exhibits high peel strength and shear strength. [Background technology]

[0002] One type of acrylic adhesive that cures reactively at room temperature is an acrylic adhesive that cures reactively by mixing peroxide and its decomposition accelerator, and is known as a second-generation acrylic adhesive (SGA). This second-generation acrylic adhesive has the advantages of developing adhesive strength in a short time, having a wide range of tolerance for the mixing ratio of each component, and having excellent adhesion to various materials such as metals and plastics, and is therefore widely used in various fields such as electrical, mechanical, automotive, construction, and civil engineering. In second-generation acrylic adhesives, which are becoming increasingly used, the use of urethane (meth)acrylate compounds has been investigated in recent years to improve their physical properties (Patent Documents 1 to 3). However, even with these techniques, they are still insufficient to meet the market demand for acrylic adhesives, and further improvements are desired.

[0003] The inventors have focused on the fact that among urethane (meth)acrylate compounds, those containing polytetramethylene glycol in the main chain have excellent low-temperature properties, and have found that the use of low-crystalline polytetramethylene glycol in particular results in excellent heat resistance, elongation of the cured product, etc. (Patent Document 4). However, since it is common for urethane (meth)acrylate compounds to have various performance improvements by increasing the molecular weight or the amount of urethane bonds in the polymer skeleton, the acrylic adhesive composition using the urethane (meth)acrylate compound has a problem that when trying to improve its performance, the acrylic adhesive composition becomes highly viscous and has poor workability. Furthermore, since the acrylic adhesive composition tends to have a high viscosity, there is also a problem that the amount of other additive components added is limited, and as a result, the desired performance cannot be obtained. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2020 / 100832 [Patent Document 2] JP 2020-41042 A [Patent Document 3] Special Publication No. 2022-526354 [Patent Document 4] International Publication No. 2022 / 249965 Summary of the Invention [Problem to be solved by the invention]

[0005] The adhesive performance requirements for products containing acrylic adhesive compositions and their cured products as components are becoming more stringent every year, and when polytetramethylene glycol-based urethane (meth)acrylate compounds are used to achieve these requirements, there is a problem that the viscosity becomes high and workability becomes poor.

[0006] An object of the present invention is to provide an acrylic adhesive composition which contains a polytetramethylene glycol-based urethane (meth)acrylate compound as an essential component, and which has low viscosity, excellent workability, and exhibits high peel strength and shear strength. [Means for solving the problem]

[0007] As a result of intensive research into solving the above problems, the inventors discovered that the above problems could be solved by an acrylic adhesive composition that uses a specific polytetramethylene glycol-based (meth)acrylate compound as an essential component, and thus completed the present invention. That is, the present invention provides the following acrylic adhesive composition containing a specific polytetramethylene glycol-based (meth)acrylate compound as an essential component, a cured product thereof, and a product having the cured product as a constituent element. [Item 1] (A) a polytetramethylene glycol-based urethane (meth)acrylate compound having a (meth)acrylate group at its terminal, the polytetramethylene glycol-based urethane (meth)acrylate compound being obtained by reacting a polytetramethylene glycol-based prepolymer obtained by reacting (a) a polyol compound with (b) a polyisocyanate compound in a molar ratio of (b) component / (a) component in the range of 0 to 0.5, with (c) a terminal (meth)acrylate agent; (B) a polymerizable vinyl monomer, (C) organic peroxide, (D) a reducing agent, An acrylic adhesive composition comprising as an essential component: [Item 2] The acrylic adhesive composition according to Item 1, in which, when the total amount of the (A) component and the (B) component is 100 parts by weight, the (A) component is 5 to 60 parts by weight, the (B) component is 40 to 95 parts by weight, the (C) component is 0.05 to 10 parts by weight, and the (D) component is 0.01 to 10 parts by weight. [Item 3] The (b) polyisocyanate compound is selected from the following (i) to (iv); (i) an aliphatic polyisocyanate compound, (ii) alicyclic polyisocyanate compounds, (iii) biuret, nurate, adduct, allophanate, carbodiimide or polymer of an aliphatic polyisocyanate compound; (iv) Biuret, nurate, adduct, allophanate, carbodiimide or polymer of an alicyclic polyisocyanate compound; Item 3. The acrylic adhesive composition according to item 1 or 2, wherein the acrylic adhesive composition is one or more selected from the group consisting of: [Item 4] The acrylic adhesive composition according to any one of Items 1 to 3, wherein the (c) terminal (meth)acrylate agent is an isocyanate group-containing (meth)acrylate compound or a carboxyl group-containing (meth)acrylate compound. [Item 5] The acrylic adhesive composition according to any one of Items 1 to 4, wherein the (B) polymerizable vinyl monomer includes a (meth)acryloyl-based monomer having one or more (meth)acryloyl groups. [Item 6] The acrylic adhesive composition according to any one of Items 1 to 5, wherein the (B) polymerizable vinyl monomer contains methacrylic acid. [Item 7] The acrylic adhesive composition according to any one of Items 1 to 6, wherein the (B) polymerizable vinyl monomer comprises a (meth)acrylic acid ester having a phosphate group. [Item 8] The acrylic adhesive composition according to any one of Items 1 to 7, further comprising (E) a core-shell rubber. [Item 9] A cured product of the acrylic adhesive composition according to any one of items 1 to 8. [Item 10] A product having the cured product according to item 9 as a component. Effect of the Invention

[0008] The present invention provides an acrylic adhesive composition that has low viscosity, excellent workability, and exhibits high peel strength and shear strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The acrylic adhesive composition of the present invention, its cured product, and a product having the cured product as a component thereof will be described below. In the present invention, "(meth)acrylic" means "acrylic" and "methacrylic", "(meth)acrylate" means "acrylate" and "methacrylate", and "(meth)acryloyl group" means "acryloyl group" and "methacryloyl group", respectively.

[0010] [Acrylic adhesive composition] The acrylic adhesive composition of the present invention comprises: (A) a polytetramethylene glycol-based urethane (meth)acrylate compound having a terminal (meth)acrylate group, the polytetramethylene glycol-based urethane (meth)acrylate compound being obtained by reacting (a) a polyol compound with (b) a polyisocyanate compound in a molar ratio of component (b) / component (a) in the range of 0 to 0.5 to obtain a polytetramethylene glycol-based prepolymer, with (c) a terminal (meth)acrylate agent; (B) a polymerizable vinyl monomer, (C) organic peroxide, (D) a reducing agent, The acrylic adhesive composition may further contain (E) a core-shell rubber.

[0011] <(A) Polytetramethylene glycol-based urethane (meth)acrylate compound having a (meth)acrylate group at its terminal> (A) A polytetramethylene glycol-based urethane (meth)acrylate compound having a (meth)acrylate group at its terminal is a polytetramethylene glycol-based urethane (meth)acrylate compound obtained by reacting at least (a) a polyol compound and (b) a polyisocyanate compound in a molar ratio of component (b) / component (a) in the range of 0 to 0.5 to obtain a polytetramethylene glycol-based prepolymer, with (c) a terminal (meth)acrylate agent.

[0012] <(a) Polyol compound> The (a) polyol compound may contain polytetramethylene glycol, and may contain other polyols in addition to polytetramethylene glycol.

[0013] (Polytetramethylene glycol) Polytetramethylene glycol is represented by the following formula (1); HO-(CH2CH2CH2CH2O) n -H (1) (In formula (1), n ​​is the number of repeating units.) For example, commercially available compounds from Mitsubishi Chemical Corporation, BASF, Dalian Chemical Industry Co., Ltd., LYCRA, Hodogaya Chemical Co., Ltd., etc. can be used.

[0014] The number average molecular weight of polytetramethylene glycol is not particularly limited, for example, 500 or more, preferably 1,000 or more, more preferably 1,500 or more because the adhesive strength of the acrylic adhesive composition using the obtained polytetramethylene glycol-based urethane (meth)acrylate compound is excellent, and for example, 10,000 or less, preferably 7,000 or less, more preferably 5,000 or less, even more preferably 3,500 or less because it is easily available.

[0015] (Other polyols) The polyol other than polytetramethylene glycol that may be contained in the (a) polyol compound is not particularly limited as long as it is a polyol having two or more hydroxyl groups. For example, ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,2-pentanediol, 1,3-pentanediol, 1,4-pentanediol, 1,5-pentanediol, 1,6-hexanediol, 1,5-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11 aliphatic polyols such as 1,12-dodecanediol, 2-methyl-1,3-propanediol, neopentyl glycol, 2-methyl-1,5-pentanediol, 3-methyl-1,5-pentanediol, 2-ethyl-1,6-hexanediol, 2-methyl-1,3-pentanediol, 2-methyl-1,8-octanediol, 1-methyl-1,8-octanediol, glycerin, trimethylolpropane, and pentaerythritol; For example, 1,3-cyclohexanediol, 1,4-cyclohexanediol, 1,3,5-cyclohexanetriol, 1,4-cyclohexanedimethanol, 1,2-cyclopentanediol, 1,3-cyclopentanediol, 1,1-cyclohexanedimethanol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, 1,2-cyclooctanediol, 1,5-cyclooctanediol, 5-norbornene-2,2-dimethanol, 5-norbornene-2,2-dimethanol, alicyclic polyols such as norbornane-2,3-dimethanol, norbornane-2,3-dimethanol, norbornane-2,5-dimethanol, 2,6-decahydronaphthalenedimethanol, 1,3-adamantanediol, 1,4-adamantanediol, 2,4-adamantanediol, tricyclodecane dimethanol, polyoxyethylene-bisphenol A ether, polyoxypropylene-bisphenol A ether, polyoxyethylene-polyoxypropylene-bisphenol A ether, and hydrogenated bisphenol A; For example, polyalkylene glycols such as diethylene glycol, dipropylene glycol, tripropylene glycol, and triethylene glycol; For example, polymer polyols such as polycarbonate polyols, polyether polyols, polyester polyols, polyurethane polyols, and polyolefin polyols, which have a weight average molecular weight of 300 or more and 10,000 or less; and the like.

[0016] The amount of the other polyol is, for example, 90% by mass or less, preferably 70% by mass or less, more preferably 50% by mass or less, and further preferably 20% by mass or less, when the total amount of the (a) polyol compound is taken as 100% by mass. The other polyol may not be used. In addition, copolymers of polytetramethylene glycol and other compounds, such as polyoxytetramethylene-polyoxyethylene glycol copolymers, polyoxytetramethylene-polyoxypropylene glycol copolymers, and trimethylolpropane-tris(polyoxytetramethylene-polyoxypropylene) ether copolymers, may be used as part or all of the (a) polyol compound.

[0017] <(b) Polyisocyanate compound> The polyisocyanate compound is not particularly limited as long as it is a compound having two or more isocyanate groups. For example, 1,6-hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, 1,4-hexamethylene diisocyanate, 1,5-pentamethylene diisocyanate, 2-methyl-1,5-pentyl diisocyanate, 3-methyl-1,5-pentyl diisocyanate, methylene diisocyanate, 1,2-dimethylene diisocyanate, 1,3-trimethylene diisocyanate, aliphatic polyisocyanate compounds such as 1,18-octadecane diisocyanate, 1,4-tetramethylene diisocyanate, 1,10-decamethylene diisocyanate, bis(2-isocyanatoethyl) fumarate, lysine diisocyanate (hexanoic acid-2,6-diisocyanate), 1,6,11-undecane triisocyanate, 1,8-diisocyanato-4-isocyanatomethyloctane, and 1,3,6-hexamethylene triisocyanate; For example, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate, 2,4-diphenylmethane diisocyanate, 3,3'-dimethyl-4,4'-diphenylmethane diisocyanate, polymethylene polyphenylene polyisocyanate, 4,4'-diphenylether diisocyanate, 2,4'-diphenylether diisocyanate, 4,4'-biphenylene diisocyanate, 3,3'-dimethyl-4,4'-biphenylene diisocyanate, 2,6-dimethyl-4,4'-biphenylene diisocyanate, 3,3'-dimethoxy-4,4'-biphenylene diisocyanate, o-xylylene diisocyanate, Aromatic polyisocyanate compounds such as m-xylylene diisocyanate, p-xylylene diisocyanate, tetramethylxylylene diisocyanate, 1,5-naphthalene diisocyanate, dianisidine diisocyanate, o-phenyl diisocyanate, m-phenyl diisocyanate, p-phenyl diisocyanate, halogenated phenyl diisocyanates, cumene-2,4-diisocyanate, 4-methoxy-1,3-phenylene diisocyanate, 4-ethoxy-1,3-phenylene diisocyanate, 5,6-dimethyl-1,3-phenylene diisocyanate, benzidine diisocyanate, 1,4-anthracene diisocyanate, 9,10-anthracene diisocyanate, and 4,4'-diisocyanate benzyl; For example, alicyclic polyisocyanate compounds such as methylcyclohexane-2,4-diisocyanate, methylcyclohexane-2,6-diisocyanate, 1,4-(isocyanatemethyl)cyclohexane, 1,3-(isocyanatemethyl)cyclohexane, 1,2-(isocyanatemethyl)cyclohexane, isophorone diisocyanate, dimer acid diisocyanate, bicycloheptane triisocyanate, 4,4'-dicyclohexylmethane diisocyanate, norbornyl diisocyanate, norbornene methane diisocyanate, 1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate, and hydrogenated products of the diisocyanates having an aromatic ring; Polyisocyanate derivatives such as biuret, nurate, adduct, allophanate, carbodiimide and polymers of these polyisocyanate compounds; and the like.

[0018] Among these, the following (i) to (iv) are preferable: (i) an aliphatic polyisocyanate compound, (ii) alicyclic polyisocyanate compounds, (iii) Aliphatic polyisocyanate derivatives which are biuret, nurate, adduct, allophanate, carbodiimide or polymers of aliphatic polyisocyanate compounds; (iv) One or more selected from the group consisting of biuret, nurate, adduct, allophanate, carbodiimide and polymeric alicyclic polyisocyanate derivatives of alicyclic polyisocyanate compounds. More preferably, 1,6-hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, 1,5-pentamethylene diisocyanate, 2-methyl-1,5-pentyl diisocyanate, 3-methyl-1,5-pentyl diisocyanate, 1,4-tetramethylene diisocyanate, lysine diisocyanate (hexanoic acid-2,6-diisocyanate), methylcyclohexane-2,4-diisocyanate, methylcyclohexane-2,6-diisocyanate, 1,4-(isocyanatemethyl)cyclohexane, 1,3-(isocyanatemethyl)cyclohexane, 1,2-(isocyanatemethyl)cyclohexane, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, The polyisocyanate compound may be one or more selected from the group consisting of biuret, nurate, adduct, allophanate, carbodiimide and polymers of these polyisocyanate compounds, and more preferably one or more selected from the group consisting of 1,6-hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, 1,5-pentamethylene diisocyanate, 1,4-tetramethylene diisocyanate, 1,4-(isocyanatemethyl)cyclohexane, 1,3-(isocyanatemethyl)cyclohexane, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, biuret, nurate, adduct, allophanate, carbodiimide and polymers of these polyisocyanate compounds.

[0019] As these polyisocyanate compounds, various commercially available products can be used, for example, one or more selected from the group consisting of the Duranate series (e.g., D101, D101, A201, etc.; manufactured by Asahi Kasei Corporation), the Stabio series (manufactured by Mitsui Chemicals, Inc.), the Tolonate series (e.g., XFLO100, HDT, IDT 70 B, HDB-LV, etc.; manufactured by VENCOREX Corporation), and the Fortimo series (manufactured by Mitsui Chemicals, Inc.). For example, some of the Stabio series and Tolonate series are bio-based isocyanates, and by using these, it is possible to increase the biomass content of polytetramethylene glycol-based (meth)acrylate compounds.

[0020] ((a) Molar ratio of polyol compound to (b) polyisocyanate compound) The molar ratio of the (a) polyol compound to the (b) polyisocyanate compound, that is, the (b) component / (a) component molar ratio, is not particularly limited as long as it is in the range of 0 to 0.5. The ratio of the (b) polyisocyanate compound to 1.0 mol of the (a) polyol compound is 0.0 mol or more, preferably 0.1 mol or more, more preferably 0.15 mol or more, and 0.5 mol or less, preferably 0.4 mol or less.

[0021] If the molar ratio of component (b) / component (a) is greater than 0.5, the molecular weight of the oligomer obtained from the polyol compound (a) and the polyisocyanate compound becomes large, resulting in an increase in viscosity, and thus a problem arises in that when the composition is used as an acrylic adhesive composition, workability decreases. The molar ratio of (b) polyisocyanate component / (a) polyol component in conventionally known urethane (meth)acrylate compounds is in the range of 0.5 to 3.0, and is particularly considered to be in the range of 1.0 to 2.0 (for example, paragraph

[0074] of WO 2020 / 054582, paragraph

[0050] of JP 2020-164586 A, paragraph

[0013] of WO 2013 / 099766, etc.). This is because, since isocyanate groups generally remain at the ends of the prepolymer obtained by using an excess of the polyisocyanate component, subsequent functional group introduction can be performed with a monool compound or a monoamine compound, which is inexpensive and easy to control the reaction. However, contrary to the common sense of those skilled in the art, the inventors have found that by leaving the hydroxyl groups of the polyol component, the obtained prepolymer and the finally prepared acrylic adhesive composition have low viscosity and excellent performance as an adhesive.

[0022] <(c) Terminal (meth)acrylate Agent> (c) The terminal (meth)acrylate agent is a component that introduces a (meth)acryloyl group to the end of a polytetramethylene glycol-based prepolymer, which is a reaction product of (a) a polyol compound containing polytetramethylene glycol and (b) a polyisocyanate compound. The (c) terminal (meth)acrylate agent includes an isocyanate group-containing (meth)acrylate compound or a carboxyl group-containing (meth)acrylate compound, but any component that introduces a (meth)acryloyl group to the end of the prepolymer can be used.

[0023] The amount of (c) terminal (meth)acrylate agent used is not particularly limited as long as it is an amount that can introduce a (meth)acrylate group to the end of the prepolymer, which is the reaction product of (a) polyol compound containing polytetramethylene glycol and (b) polyisocyanate compound. When the molar ratio of (a) polyol compound / (b) polyisocyanate compound of the present invention is 0 to 0.5, the end of the obtained prepolymer is a hydroxyl group derived from the polyol compound, and when the molar amount of this terminal hydroxyl group is X mol, the amount of (c) terminal (meth)acrylate agent introduced is preferably in the range of 0.1X to 1.0X mol, preferably 0.5X mol or more, more preferably 0.8X mol or more, and most preferably 1.0X mol. The molar amount of the (c) terminal (meth)acrylate agent introduced is the amount of terminal (meth)acrylate agent bonded to the prepolymer. When a compound with low reactivity is used, an excess of terminal (meth)acrylate agent may be used for the reaction, and the excess terminal (meth)acrylate agent may be removed after the reaction. In some cases, it is also possible to form an acrylic adhesive composition in a state where the excess terminal (meth)acrylate agent remains unreacted in the system.

[0024] (Isocyanate group-containing (meth)acrylate compound) The isocyanate group-containing (meth)acrylate compound is not particularly limited as long as it is a compound having one or more isocyanate groups or blocked isocyanate groups and one or more (meth)acryloyl groups in the molecule. For example, 2-isocyanatoethyl (meth)acrylate, 3-isocyanatopropyl (meth)acrylate, 2-isocyanato-1-methylethyl (meth)acrylate, 2-isocyanato-1,1-dimethylethyl (meth)acrylate, 5-(meth)acryloyloxy-3-oxypentyl isocyanate, 4-isocyanatocyclohexyl (meth)acrylate, 2-(2-isocyanatoethoxy)ethyl (meth)acrylate, 1,1-bis((meth)acryloyloxymethyl)ethoxyethyl (meth)acrylate, and the like. Examples of the blocking agent include one or more selected from the group consisting of ethyl isocyanate, 2-(2-(meth)acryloyloxyethyloxy)ethyl isocyanate, reaction products of the hydroxyl group-containing (meth)acrylate group with a polyol compound, compounds in which the isocyanate group of these compounds is masked with a blocking agent, 2-[(3,5-dimethylpyrazolyl)carbonylamino]ethyl (meth)acrylate, and 2-(0-[1'-methylpropylideneamino]carboxyamino)ethyl (meth)acrylate.

[0025] (Carboxyl group-containing (meth)acrylate compound) The carboxyl group-containing (meth)acrylate compound is not particularly limited as long as it is a compound having one or more carboxyl groups and one or more (meth)acryloyl groups in the molecule. For example, unsaturated monocarboxylic acids such as acrylic acid, methacrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, ethyl succinic acid (meth)acrylate, ethyl hexahydrophthalic acid (meth)acrylate, ethyl phthalic acid (meth)acrylate, propyl succinic acid (meth)acrylate, propyl hexahydrophthalic acid (meth)acrylate, propyl phthalic acid (meth)acrylate, ethyl tetrahydrophthalic acid (meth)acrylate, propyl tetrahydrophthalic acid (meth)acrylate, and crotonic acid; unsaturated dicarboxylic acids such as fumaric acid, maleic acid, and itaconic acid; maleic anhydride; butenedioic acid monocyclic alkyl esters such as monocyclopentyl fumarate, monocyclohexyl fumarate, monocyclopentyl maleate, and monocyclohexyl maleate; and itaconic acid monoesters such as monomethyl itaconate, monoethyl itaconate, mono-n-butyl itaconate, and monocyclohexyl itaconate. Among these, unsaturated monocarboxylic acids such as acrylic acid, methacrylic acid, and carboxyethyl (meth)acrylate are preferred because of their excellent reactivity and easy availability.

[0026] (number average molecular weight) The number average molecular weight of the polytetramethylene glycol-based urethane (meth)acrylate compound having a (meth)acrylate group at the end (A) is not particularly limited, and is, for example, 1,000 or more, preferably 2,000 or more, more preferably 2,500 or more, and is, for example, 30,000 or less, preferably 20,000 or less, more preferably 15,000 or less. The number average molecular weight of (A) a polytetramethylene glycol-based urethane (meth)acrylate compound having a (meth)acrylate group at its terminal can be adjusted by the molecular weight of each of the (a) polyol compound and the (b) polyisocyanate compound and the molar amounts of the (a) polyol compound and the (b) polyisocyanate compound charged. Furthermore, the number average molecular weight can be adjusted to a predetermined range by selecting the type and amount of the reaction catalyst, adjusting the reaction time, reaction temperature, etc., as necessary.

[0027] <(B) Polymerizable vinyl monomer> The polymerizable vinyl monomer can be any of various polymerizable vinyl monomers without any particular limitations. Specifically, any of various polymerizable vinyl monomers capable of radical polymerization can be used. Examples of the polymerizable vinyl monomer include (meth)acrylic acid esters, styrene, α-alkylstyrene, divinylbenzene, vinyl ether, divinyl ether, maleic anhydride, maleic acid esters, maleimide compounds, vinyl acetate, diallyl phthalate, diallyl fumarate, triallyl isocyanurate, vinylbenzyl butyl ether, vinylbenzyl hexyl ether, divinylbenzyl ether, allyl (meth)acrylate, N-vinylpyrrolidone, 2-vinylpyridine, vinyl acetate, vinyl propionate, and the like. Among these, (meth)acrylic acid esters are preferred from the viewpoint of good reactivity. Examples of the (meth)acrylic acid ester include the following compounds (i) to (vi).

[0028] (i) The general formula is ZOR 1 Monomer represented by In formula (i), Z represents a (meth)acryloyl group, R 1 represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, a cycloalkyl group, a benzyl group, a phenyl group, a tetrahydrofurfuryl group, a glycidyl group, a dicyclopentanyl group, a dicyclopentenyl group, a (meth)acryloyl group, or an isobornyl group. Examples of the monomer represented by the general formula (i) include methyl (meth)acrylate, octyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, glycerol (meth)acrylate, glycerol di(meth)acrylate, glycerol formal (meth)acrylate, isobornyl (meth)acrylate, adamantyl (meth)acrylate, norbornyl (meth)acrylate, methyl-2-allyloxy (meth)acrylate, 2-phenoxymethyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, phenyl (meth)acrylate, Examples of the acrylates include methoxyethyl acrylate, ethoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, glycidyl (meth)acrylate, 4-(meth)acryloyloxymethyl-2-cyclohexyl-1,3-dioxolane, (2-methyl-2-ethyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, (3-ethyloxetan-3-yl)methyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate glycidyl ether, (meth)acryloylmorpholine, N-(meth)acryloyloxyethyl hexahydrophthalimide, pentamethylpiperidyl (meth)acrylate, N-(meth)acryloyloxysuccinimide, N-(meth)acryloyloxyphthalimide, and (meth)acrylic acid.

[0029] (ii) The general formula is ZO-(R 2 O) p -R 1 The monomer represented by In formula (ii), Z and R 1 is the same as above. Also, R 2 is -C2H4-, -C3H6-, -CH2CH(CH3)-, -C4H8-, or -C6H 12 -, and p represents an integer of 1 to 25. Examples of the monomer represented by the general formula (ii) include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, ethoxyethyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, phenoxyethyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, tripropylene glycol di(meth)acrylate, pentaerythritol (meth)acrylate, and ethylene glycol monomethyl ether (meth)acrylate. acrylate, ethylene glycol monoethyl ether (meth)acrylate, ethylene glycol monobutyl ether (meth)acrylate, diethylene glycol monomethyl ether (meth)acrylate, diethylene glycol monoethyl ether (meth)acrylate, diethylene glycol monobutyl ether (meth)acrylate, diethylene glycol mono 2-ethylhexyl ether (meth)acrylate, dipropylene glycol monomethyl ether (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinate, and 2-(meth)acryloyloxyethyl phthalate.

[0030] (iii) the general formula is Z-(OR 2 ) q -O-Ph-C(R 3 )2-Ph-O-(R 2 O) q -Z Monomer In formula (iii), Z and R 2 is the same as above. R 3 represents hydrogen or an alkyl group having 1 to 4 carbon atoms, q represents an integer of 0 to 8, and Ph represents a phenylene group. Examples of the monomer represented by general formula (iii) include EO-modified epoxy (meth)acrylates such as 2,2-bis(4-(meth)acryloxyphenyl)propane, 2,2-bis(4-(meth)acryloxyethoxyphenyl)propane, 2,2-bis(4-(meth)acryloxydiethoxyphenyl)propane, 2,2-bis(4-(meth)acryloxypropoxyphenyl)propane, and 2,2-bis(4-(meth)acryloxypolyethoxyphenyl)propane.

[0031] (iv) Acrylamide Monomer (iv) Examples of the acrylamide monomer include (meth)acrylamide, dimethyl(meth)acrylamide, diethyl(meth)acrylamide, 2-hydroxyethyl(meth)acrylamide, 2-hydroxyethyl-N-methyl(meth)acrylamide, 3-hydroxypropyl(meth)acrylamide, N-methyl(meth)acrylamide, N-hydroxyethyl(meth)acrylamide, N-ethyl(meth)acrylamide, N-methylol(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-dibutyl(meth)acrylamide, N,N-diisobutyl(meth)acrylamide, N,N-di-tert-butyl(meth)acrylamide, N,N-dimethylaminoethyl(meth)acrylamide, dimethylaminopropyl(meth)acrylamide, isopropyl(meth)acrylamide, diacetone(meth)acrylamide, and acryloylmorpholine.

[0032] (v) Polyfunctional acrylates other than the above (i) to (iv) Examples of the polyfunctional acrylates contained in (v) include ethylene glycol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, 1,4-butylene glycol di(meth)acrylate, 1,6-hexane glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, ethylene oxide modified neopentyl glycol di(meth)acrylate, propylene oxide modified neopentyl glycol di(meth)acrylate, bisphenol A di(meth)acrylate, ethylene oxide modified bisphenol A di(meth)acrylate, epichlorohydrin modified bisphenol A di(meth)acrylate, ethylene oxide modified bisphenol S di(meth)acrylate, hydroxypivalic acid ester neopentyl glycol di Acrylates, caprolactone-modified hydroxypivalic acid ester neopentyl glycol diacrylate, neopentyl glycol-modified trimethylolpropane di(meth)acrylate, stearic acid-modified pentaerythritol di(meth)acrylate, dicyclopentenyl diacrylate, ethylene oxide-modified dicyclopentenyl di(meth)acrylate, di(meth)acryloyl isocyanurate, trimethylolpropane tri(meth)acrylate, glycerin tri(meth)acrylate, pentaerythritol tri(meth)acrylate ditrimethylolpropane tetra(meth)acrylate, ditrimethylolpropane hexa(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, isocyanuric acid di(meth)acrylate, isocyanuric acid tri(meth)acrylate,Examples of the acrylate include triazine tri(meth)acrylate, tris(2-hydroxyethyl)isocyanurate tri(meth)acrylate, propoxylated glycerol tri(meth)acrylate, and propoxylated pentaerythritol tri(meth)acrylate.

[0033] (vi) Oligomers having (meth)acrylate groups Examples of oligomers contained in (vi) include poly(meth)acrylic acid ester oligomers having a (meth)acrylate group, polyester (meth)acrylate oligomers, urethane (meth)acrylate oligomers other than the component (A) of the present invention, epoxy (meth)acrylate oligomers, polycarbonate oligomers, epoxy oligomers, saturated hydrocarbon oligomers, and unsaturated hydrocarbon oligomers. Specific examples of these oligomers include those described in paragraphs

[0029] to

[0039] of JP 2018-188602 A.

[0034] These polymerizable vinyl monomers of component (B), such as the polymerizable vinyl monomers listed in (i) to (vi) above, may be used alone or in combination of two or more. Also, each of the polymerizable vinyl monomers listed in (i) to (vi) above may be used alone or in combination of two or more.

[0035] As the (meth)acrylic acid ester, those having a hydroxyl group, an alicyclic alkyl group, or an aromatic alkyl group are preferred because the adhesive cured product has a high Tg and excellent adhesive strength.Moreover, in terms of availability, methyl (meth)acrylate, ethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, and isobornyl (meth)acrylate are preferred.

[0036] The amount of the polymerizable vinyl monomer is not particularly limited, but is preferably 40 to 95 parts by weight, and more preferably 50 to 90 parts by weight, when the total amount of the (A) component and the (B) component is taken as 100 parts by weight. If the amount of the polymerizable vinyl monomer is less than 40 parts by weight, the viscosity of the acrylic composition increases, and the workability tends to be poor, and the adhesiveness may also decrease.

[0037] In addition, it is preferable that the adhesive contains methacrylic acid as the polymerizable vinyl monomer (B), since this results in a cured product of the adhesive having a high Tg and excellent adhesive strength, and furthermore improves heat resistance. The amount of methacrylic acid is preferably 0.1 to 30 parts by weight, and more preferably 5 to 25 parts by weight, based on 100 parts by weight of the total amount of components (A) and (B). If the amount of methacrylic acid exceeds 30 parts by weight, the peel strength of the cured product may decrease.

[0038] Furthermore, it is preferable that the polymerizable vinyl monomer (B) contains acryloylmorpholine, since this leads to a high Tg of the cured product of the adhesive, excellent adhesive strength, and improved elongation. The amount of acryloylmorpholine is preferably 1 to 50 parts by weight, more preferably 5 to 25 parts by weight, based on 100 parts by weight of the total amount of components (A) and (B). If the amount of acryloylmorpholine exceeds 50 parts by weight, the cured product may become brittle and the adhesive strength may decrease.

[0039] In order to provide excellent adhesion and adhesive strength to metal substrates, it is preferable that the polymerizable vinyl monomer (B) contains a (meth)acrylic acid ester containing a phosphate group, specifically, 2-methacryloyloxyethyl acid phosphate, 2-methacryloyloxypropyl acid phosphate, bis(2-methacryloyloxyethyl acid)phosphate, etc. The amount of the (meth)acrylic acid ester containing a phosphate group is preferably 0.1 to 10 parts by weight, and more preferably 0.3 to 5 parts by weight, based on 100 parts by weight of the total amount of components (A) and (B). If the amount of the (meth)acrylic acid ester containing a phosphate group is less than 0.1 parts by weight, the improvement in adhesion to metal substrates may be insufficient, whereas if it exceeds 10 parts by weight, not only is it economically disadvantageous, but the storage stability of the acrylic adhesive composition may also decrease.

[0040] <(C)Organic peroxide> As the (C) organic peroxide, various organic peroxides can be used, such as t-butyl peroxybenzoate, t-butyl peroxydecanoate, cumene hydroperoxide, p-menthane hydroperoxide, t-butyl hydroperoxide, diisopropylbenzene dihydroperoxide, methyl ethyl ketone peroxide, and benzoyl peroxide.

[0041] These organic peroxides can be used alone or in combination of two or more kinds. Among these, hydroperoxides are preferred because they are stable at room temperature (25°C ± 5°C) and easy to handle, and the reaction easily starts at room temperature when used in combination with a reducing agent. Cumene hydroperoxide is particularly preferred because of its excellent stability.

[0042] The amount of the organic peroxide is preferably 0.05 to 10 parts by weight, more preferably 0.1 to 5 parts by weight, based on 100 parts by weight of the total amount of the (A) component and the (B) component. If the amount of the organic peroxide is less than 0.05 parts by weight, the curing speed may decrease. If the amount is more than 10 parts by weight, the storage stability of the acrylic adhesive composition may deteriorate.

[0043] <(D) Reducing agent> As the (D) reducing agent, various compounds that generate radicals by reacting an organic peroxide with the reducing agent can be used. Examples of the reducing agent include a reaction condensation product of an amine and an aldehyde, triethylamine, tripropylamine, tributylamine, N,N-dimethyl-p-toluidine, 2-mercaptobenzimidazole, methylthiourea, dibutylthiourea, tetramethylthiourea, ethylenethiourea, cobalt compounds such as cobalt octylate, cobalt naphthenate, cobalt acetylacetone, and cobalt acetoacetate, copper compounds such as copper naphthenate and copper versatate, and vanadium compounds.

[0044] Examples of vanadium compounds include vanadyl acetylacetonate, vanadyl stearate, vanadium naphthenate, vanadium acetylacetonate, vanadium benzoylacetonate, etc. Among these, vanadyl acetylacetonate and ethylenethiourea are preferred because of their good reactivity with hydroperoxide.

[0045] These reducing agents can be used alone or in combination of two or more. The amount of the reducing agent is preferably 0.01 to 10 parts by weight, more preferably 0.04 to 5 parts by weight, when the total amount of the (A) component and the (B) component is 100 parts by weight. If the amount of the reducing agent is less than 0.01 part by weight, the curing speed may be slow. If the amount of the reducing agent is more than 10 parts by weight, the storage stability may be reduced when the reducing agent is used together with a polymerizable vinyl monomer.

[0046] <Rubber particles> The acrylic adhesive composition of the present invention may contain fine rubber particles, preferably a core-shell rubber (E), in addition to the components (A) to (D). The rubber fine particles adjust the viscosity of the acrylic adhesive composition, impart thixotropy, and act as an impact buffer for the adhesive layer after curing. The rubber fine particles may be fine particles consisting of at least a rubber layer alone, or may be core-shell type particles having a rubber core layer and a shell layer further covered with a resin layer.

[0047] ((E) Core-shell rubber) As the (E) core-shell rubber, various core-shell rubbers can be used. In the presence of the core layer, a graft copolymerizable monomer component is graft polymerized to form a shell layer, and the resulting polymer particles can be synthesized. As the rubber for the core layer, silicone rubber, butadiene rubber, styrene-butadiene rubber, acrylic rubber, acrylonitrile-butadiene-styrene rubber (ABS), methyl methacrylate-butadiene-styrene rubber (MBS), methyl methacrylate-butadiene rubber (MB), methyl methacrylate-butyl acrylate rubber (MBA), methyl methacrylate-butyl acrylate-styrene rubber (MBAS), acrylonitrile-butyl acrylate-styrene rubber (AAS), etc. can be used, but are not limited to these. For the shell layer, generally, (meth)acrylate monomers, aromatic vinyl monomers, acrylonitrile, etc. are used, but other monomers may also be used. As for the type of rubber for the core layer and the monomer for the shell layer, one type or two or more types may be used depending on the desired properties. The blending amount of the (E) core-shell rubber is preferably 2 to 50 parts by weight, and more preferably 5 to 30 parts by weight, based on 100 parts by weight of the total amount of the (A) component and the (B) component.

[0048] <Other additives> The acrylic adhesive composition of the present invention may further contain various additives ("other additives") in addition to the components (A) to (E). Other additives include, for example, one or more selected from the group consisting of elastomers that impart toughness or flexibility to the cured product, thixotropic agents, storage stabilizers (polymerization inhibitors, antioxidants, etc.), epoxy resins, fillers, organic solvents (e.g., volatile liquids such as alcohols, esters, and hydrocarbons), flame retardants, antisagging agents, anti-precipitation agents, curing accelerators, flame retardants, anti-aging agents, heat stabilizers, light stabilizers, UV absorbers, fragrances, lubricants (waxes, etc.), antibacterial agents, antifungal agents, leveling agents, colorants, lustrous materials, adhesion promoters, tackifier resins, surface conditioners, surfactants, defoamers, wetting agents, rust inhibitors, leveling agents, chain transfer agents (polythiol compounds, etc.), viscosity adjusters, sensitizers, adhesion improvers (e.g., silane coupling agents, etc.), plasticizers, antistatic agents, etc. The amount of these additives to be added is not particularly limited as long as it does not inhibit the properties of the acrylic adhesive composition and its cured product, and a necessary amount to impart the desired properties can be used. Furthermore, paraffin, beeswax, etc. may be blended to improve the hardening property of the surface in contact with air, and various reaction accelerators and hardening regulators may be blended to adjust the hardening speed.

[0049] (Elastomer) The elastomer is not particularly limited as long as it is an elastomer that imparts toughness or flexibility to the cured product. For example, various synthetic rubbers such as acrylonitrile-butadiene-methacrylic acid copolymer, acrylonitrile-butadiene-methyl methacrylate copolymer, methyl methacrylate-butadiene-styrene copolymer (MBS resin), acrylonitrile-styrene-butadiene copolymer, acrylonitrile-butadiene rubber, urethane rubber, styrene-butadiene rubber, chloroprene rubber, polyisoprene rubber, nitrile rubber, acrylic rubber, epichlorohydrin rubber, and butadiene rubber, natural rubber, liquid polybutadiene, terminal acrylic modified liquid polybutadiene, liquid acrylonitrile-butadiene copolymer, etc. Examples of suitable elastomers include styrene-based thermoplastic elastomers such as styrene-polybutadiene-styrene synthetic rubber, olefin-based thermoplastic elastomers such as polyethylene-EPDM synthetic rubber, urethane-based thermoplastic elastomers such as caprolactone type, adipate type, and PTMG type, polyester-based thermoplastic elastomers such as polybutylene terephthalate-polytetramethylene glycol multiblock polymer, polyamide-based thermoplastic elastomers such as nylon-polyol block copolymer and nylon-polyester block copolymer, 1,2-polybutadiene-based thermoplastic elastomer, and vinyl chloride-based thermoplastic elastomer. These elastomers can be used alone or in combination of two or more types as long as separation is not observed.

[0050] (thixotropic agent) The thixotropic agent is not particularly limited as long as it can impart thixotropy (thixotropic property). For example, thixotropic agents such as fine powder polyethylene, dibenzylidene-D-sorbitol, cellulose triacetate, stearic acid amide, amide waxes, bentonite, fine powder silica, etc. can be blended. These thixotropic agents can be used alone or in combination of two or more kinds.

[0051] (Storage stabilizer) As the storage stabilizer, various antioxidants including polymerization inhibitors can be used. Examples of the antioxidant include p-methoxyphenol, hydroquinone, benzoquinone, 2,6-di-tertiary butyl-p-cresol, 2,2'-methylenebis(4-methyl-6-tertiary butylphenol), pentaerythritol tetrakis[3-(3,5-ditertiary butyl-4-hydroxyphenyl)propionate], triphenyl phosphite, phenothiazine, and stable radical compounds such as N-isopropyl-N'-phenyl-p-phenylenediamine, 1-oxyl-2,2,6,6-tetramethylpiperidine, 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxyl, and 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine 1-oxyl. Among these, hindered phenol-based antioxidants, hydroquinone, and benzoquinone are preferred. These storage stabilizers may be used alone or in combination of two or more kinds.

[0052] (Epoxy resin) The acrylic adhesive composition of the present invention may further contain an epoxy resin. By adding an epoxy resin to the acrylic adhesive composition, the hardness of the cured product of the acrylic adhesive composition can be adjusted by the crosslinked structure, the adhesion to metal can be improved by the hydroxyl group generated by ring-opening of the epoxy group, the polymer cohesive force can be improved, and the viscosity can be reduced as a diluent. Examples of epoxy resins include bisphenol type epoxy compounds such as bisphenol A type glycidyl ether and bisphenol F type glycidyl ether, alicyclic epoxy compounds such as 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate and 3,4-epoxy-6-methylcyclohexylmethyl-3,4-epoxycyclohexane carboxylate, etc. These epoxy resins may be used alone or in combination of two or more kinds.

[0053] (Filler) A filler can be added to the acrylic adhesive composition of the present invention as a filler in order to impart mechanical strength, abrasion resistance, electrical conductivity, and thermal conductivity, and to adjust the viscosity and thixotropy of the acrylic adhesive composition. Specific examples of the filler include various fillers described in paragraphs

[0134] to

[0151] of JP-A-2006-291073. Fillers include finely powdered silica, which is reinforcing silica such as fumed silica and wet-process silica, carbon black, wood flour, pulp, cotton chips, mica, walnut shell powder, rice husk powder, graphite, white clay, silica (crystalline silica, fused silica, dolomite, anhydrous silicic acid, hydrated silicic acid, etc.), heavy calcium carbonate, colloidal calcium carbonate, magnesium carbonate, diatomaceous earth, calcined clay, clay, talc, titanium oxide, bentonite, organic bentonite, ferric oxide, red iron oxide, fine aluminum powder, flint powder, zinc oxide, activated zinc oxide, zinc powder, zinc carbonate, shirasu balloons, polyacrylic resin, polyacrylonitrile-vinylidene chloride resin, pheno Examples of suitable fillers include beads such as those made of polystyrene resin or polystyrene resin, or hollow particles thereof; inorganic hollow particles such as glass balloons, shirasu balloons, and fly ash balloons; fibrous fillers such as glass fiber, glass filament, carbon fiber, Kevlar fiber (registered trademark), and polyethylene fiber; conductive fillers such as carbon nanotubes, fullerene, conductive carbon, tin, and lithium titanate; thermally conductive fillers such as graphite, boron nitride, aluminum nitride, aluminum hydroxide, silicon nitride, alumina, magnesia, beryllia, calcium carbonate, aluminum powder, copper powder, iron powder, titanium carbide, and diamond; and sound-absorbing fillers.

[0054] The amount of these fillers is not particularly limited, but when the total amount of the (A) component and the (B) component is 100 parts by weight, it is preferable to use 0.1 to 1000 parts by weight, preferably 10 to 500 parts by weight, and particularly 10 to 100 parts by weight. If the amount is less than 0.1 parts by weight, the effect of improving the reinforcing property may not be sufficient, and if it exceeds 1000 parts by weight, the workability of the acrylic adhesive composition may decrease, but since the acrylic adhesive composition of the present invention has a low viscosity, it is possible to use a higher amount than other adhesive compositions. In addition, the fillers may be used alone or in combination of two or more kinds.

[0055] <Form of Acrylic Adhesive Composition> The form of the acrylic adhesive composition of the present invention is not particularly limited, and can be appropriately determined depending on the application, constituent components, etc.

[0056] For example, it can be a one-component acrylic adhesive composition containing (A) a polytetramethylene glycol-based urethane (meth)acrylate compound having a (meth)acrylate group at its terminal, (B) a polymerizable vinyl monomer, (C) an organic peroxide, and (D) a reducing agent.

[0057] For example, it can be a two-liquid mixed acrylic adhesive composition consisting of an A component containing (A) a polytetramethylene glycol urethane (meth)acrylate compound having a (meth)acrylate group at the end, (B) a polymerizable vinyl monomer, and (C) an organic peroxide, and a B component containing (A) a polytetramethylene glycol urethane (meth)acrylate compound having a (meth)acrylate group at the end, (B) a polymerizable vinyl monomer, and (D) a reducing agent. When the acrylic adhesive composition of the present invention is made into a two-liquid mixed acrylic adhesive composition, it is preferable that both (C) the organic peroxide and (D) the reducing agent are not simultaneously contained in the A component and / or the B component. In addition, components other than (A) to (D) may be contained in either or both of the A component and the B component. The acrylic adhesive composition of the present invention can be suitably used particularly as a two-part mixed acrylic adhesive composition.

[0058] <Method of using the acrylic adhesive composition> The acrylic adhesive composition of the present invention produces a cured adhesive product by polymerization reaction due to the action of an organic peroxide and a reducing agent, and can be used in the same manner as general acrylic adhesives. The acrylic adhesive composition of the present invention can be used in an adhesion method in which a mixture of agent A and agent B is applied to an adherend, or in an adhesion method in which agents A and B are mixed when adhering adherends that have been separately applied to them. Agent A and B can be mixed using a static mixer or mechanical mixer that has a structure capable of mixing the two agents at the tip, but the method is not limited to these.

[0059] The acrylic adhesive composition of the present invention cures quickly at room temperature due to the action of the organic peroxide and the reducing agent, but by taking into consideration and adjusting the reactivity of each component, it is possible to speed up the curing speed to shorten the working time, or conversely, to slow down the curing speed to extend the usable time. In addition, the curability at high and low temperatures can also be appropriately adjusted. The acrylic adhesive of the present invention has excellent heat resistance at high temperatures and also has excellent peel strength at low temperatures. It has excellent adhesion to various adherends, such as metals, resins, glass, ceramics, paper, cloth, fibers, wood, bamboo, and other materials, and is particularly excellent in adhesion to metals such as iron and aluminum, wood, concrete, and composite plastics such as CFRP, GFRP, and FRP. It also has excellent adhesion to oily surfaces. It also has excellent durability against heat aging, moist heat aging, and hot water aging. In addition, since it has good shear strength and peel strength, it is expected that the bonded body will fracture ductilely rather than brittle fracture when broken. At the same time, it provides an adhesive with good impact resistance and high reliability.

[0060] The acrylic adhesive of the present invention has good storage stability and low viscosity, so that it is excellent in dischargeability from a container, mixability, and workability. Furthermore, by taking advantage of its low viscosity, it is possible to highly fill a thermally conductive filler, a conductive filler, a flame-retardant filler, etc., and it is possible to prepare an adhesive with higher performance in terms of thermal conductivity, conductivity, and flame retardancy. When used as a two-liquid mixture type, the influence of differences in weight ratio and volume ratio is sometimes small, so that the work management is easy. The acrylic adhesive of the present invention can be used in various fields such as various electric and electronic fields, automobiles, airplanes, ships, motorcycles, trains, machines, buildings, civil engineering, office supplies, and household goods. A variety of products can be provided that contain the cured acrylic adhesive composition of the present invention as a component.

[0061] [Cured product] The cured product of the present invention is obtained by curing the acrylic adhesive composition of the present invention. The cured product of the acrylic adhesive composition is formed by initiating a polymerization reaction of the acrylic adhesive composition due to the action of (C) an organic peroxide and (D) a reducing agent, which are essential components of the acrylic adhesive composition.

[0062] [Products containing the cured material as a component] A product having as a component thereof a cured product of the acrylic adhesive composition of the present invention is a product obtained by bonding with the acrylic adhesive composition of the present invention. The products are produced by bonding the above-mentioned various adherends with the acrylic adhesive composition of the present invention, and contain the cured acrylic adhesive composition as a constituent element. Examples of products include electric and electronic devices, electric and electronic parts, machine parts, vehicle parts, and vehicle interior materials. EXAMPLES

[0063] The following examples are given for more specific explanation. It goes without saying that these examples are merely illustrative and should not be interpreted as limiting. Unless otherwise specified, "%" means "% by weight" and "parts" means "parts by weight."

[0064] [Measurement method] <Viscosity> For the acrylic adhesive composition in Example 1, the viscosity was measured at 23°C using a B-type viscometer (TVB-15M type viscometer manufactured by Toki Sangyo Co., Ltd.). For the viscosity of the acrylic adhesive composition other than Example 1, the viscosity of Agent B was measured using a Brookfield parallel plate type rotational viscometer at a measurement temperature of 23°C, a used plate of 20 mmφ, a gap of 0.175 mm, and a rotation speed of 100 (1 / s). Taking the value of Example 1 as 100, it was evaluated as a relative value.

[0065] <Tensile shear adhesive strength> After surface polishing with sandblasting, two SPCC steel plates (width 25 mm × length 100 mm × thickness 1.6 mm) surface-treated with acetone were prepared. The mixed acrylic adhesive was uniformly applied to one of them in an area of 25 mm × 12.5 mm, and then bonded to the other SPCC steel plate to prepare a test piece. The thickness of the adhesive layer was adjusted to 0.23 mm. Thereafter, it was cured for 1 day or more in a 23°C environment, and in accordance with JIS K 6850, the tensile shear adhesive strength was measured at a tensile speed of 2.5 mm / min and 23°C.

[0066] <T-peel adhesive strength> After surface polishing with sandblasting, two SPCC steel plates (width 25 mm × length 150 mm × thickness 0.5 mm) surface-treated with acetone were prepared. The mixed acrylic adhesive was uniformly applied to one of them, and then bonded to the other SPCC steel plate to prepare a test piece. The thickness of the adhesive layer was adjusted using glass beads with a diameter of 0.2 mmφ. Thereafter, it was cured for 1 day or more in a 23°C environment, and in accordance with JIS K 6854, the tensile T-peel adhesive strength was measured at a tensile speed of 50 mm / min and 23°C.

[0067] [Synthesis example] <Synthesis example 1> Synthesis of polytetramethylene glycol-based urethane (meth) acrylate compound UA1 In a 500mL four-necked separable flask equipped with a stirrer, a thermometer, and a condenser, (a) 51.6mmol of polytetramethylene glycol with a molecular weight of 2900 was weighed as a polyol compound, and the mixture was stirred at 120°C under high vacuum for 3 hours to remove the moisture contained in the polyol. After cooling the system to room temperature, 150g of toluene, (b) 19.6mmol of hexamethylene diisocyanate as a polyisocyanate compound, and 100ppm of tin catalyst as a catalyst were added to the polyol compound under a nitrogen stream. The reaction was carried out at 80°C for 3 hours under a nitrogen stream to synthesize a urethane prepolymer. The temperature of the reaction solution was cooled to 50°C or less, and (c) 96.7mmol of 2-methacryloyloxyethyl isocyanate was added as a terminal (meth)acrylate agent, and the reaction was carried out at 80°C for 2 hours. The solvent and excess 2-methacryloyloxyethyl isocyanate were removed under reduced pressure to obtain a polytetramethylene glycol-based urethane (meth)acrylate compound UA1. The molar ratio (b) / (a) of (a) the polyol compound to (b) the polyisocyanate compound in the polytetramethylene glycol-based urethane (meth)acrylate compound UA1 was 0.379.

[0068] <Synthesis Example 2> Synthesis of polytetramethylene glycol-based urethane (meth)acrylate compound UA2 A polytetramethylene glycol-based urethane (meth)acrylate compound UA2 was obtained in the same manner as in Synthesis Example 1, except that 52.8 mmol of a polytetramethylene glycol / poly(3-methyl)tetramethylene glycol copolymer having a molecular weight of 3000 was added as (a) the polyol compound, and 96.7 mmol of 2-acryloyloxyethyl isocyanate was added as (c) the terminal (meth)acrylating agent. The molar ratio (b) / (a) of the (a) polyol compound to the (b) polyisocyanate compound in the obtained polytetramethylene glycol-based urethane (meth)acrylate compound UA2 was 0.371.

[0069] <Synthesis Example 3> Synthesis of polytetramethylene glycol-based urethane (meth)acrylate compound UA3 A polytetramethylene glycol-based urethane (meth)acrylate compound UA3 was obtained in the same manner as in Synthesis Example 1, except that the (b) polyisocyanate compound was not used and 2-methacryloyloxyethyl isocyanate was directly reacted with both ends of the (a) polyol compound. The molar ratio (b) / (a) of the (a) polyol compound to the (b) polyisocyanate compound in the obtained polytetramethylene glycol-based urethane (meth)acrylate compound UA3 was 0.

[0070] <Synthesis Example 4> Synthesis of polytetramethylene glycol-based urethane (meth)acrylate compound UA4 A polytetramethylene glycol-based urethane (meth)acrylate compound UA4 was obtained in the same manner as in Synthesis Example 1, except that trimethylhexamethylene diisocyanate was used as the (b) polyisocyanate compound. The molar ratio (b) / (a) of the (a) polyol compound to the (b) polyisocyanate compound in the obtained polytetramethylene glycol-based urethane (meth)acrylate compound UA4 was 0.379.

[0071] <Synthesis Example 5> Synthesis of polytetramethylene glycol-based urethane (meth)acrylate compound UA5 A polytetramethylene glycol-based urethane (meth)acrylate compound UA5 was obtained in the same manner as in Synthesis Example 1, except that biomass diisocyanate (product name Tolonate X FLO 100, manufactured by Vencorex) was used as the (b) polyisocyanate compound. The molar ratio (b) / (a) of the (a) polyol compound to the (b) polyisocyanate compound in the obtained polytetramethylene glycol-based urethane (meth)acrylate compound UA5 was 0.379.

[0072] <Synthesis Example 6> Synthesis of polytetramethylene glycol-based urethane (meth)acrylate compound UA6 A polytetramethylene glycol-based urethane (meth)acrylate compound UA6 was obtained in the same manner as in Synthesis Example 1, except that diphenylmethane diisocyanate was used as the (b) polyisocyanate compound. The molar ratio (b) / (a) of the (a) polyol compound to the (b) polyisocyanate compound in the obtained polytetramethylene glycol-based urethane (meth)acrylate compound UA6 was 0.379.

[0073] <Synthesis Example 7> Synthesis of polytetramethylene glycol-based urethane (meth)acrylate compound UA7 A polytetramethylene glycol-based urethane (meth)acrylate compound UA7 was obtained in the same manner as in Synthesis Example 1, except that 77.4 mmol of a polytetramethylene glycol / poly(3-methyl)tetramethylene glycol copolymer having a molecular weight of 2000 was used as the (a) polyol compound, and 65.2 mmol of hexamethylene diisocyanate was used as the (b) polyisocyanate compound. The molar ratio (b) / (a) of the (a) polyol compound to the (b) polyisocyanate compound in the obtained polytetramethylene glycol-based urethane (meth)acrylate compound UA7 was 0.842.

[0074] <Synthesis Example 8> Synthesis of polytetramethylene glycol-based urethane (meth)acrylate compound UA8 A polytetramethylene glycol-based urethane (meth)acrylate compound UA8 was obtained in the same manner as in Synthesis Example 1, except that 48.3 mmol of a polytetramethylene glycol / poly(3-methyl)tetramethylene glycol copolymer having a molecular weight of 3000 was used as the (a) polyol compound, and 35.8 mmol of hexamethylene diisocyanate was used as the (b) polyisocyanate compound. The molar ratio (b) / (a) of the (a) polyol compound to the (b) polyisocyanate compound in the obtained polytetramethylene glycol-based urethane (meth)acrylate compound UA8 was 0.741.

[0075] <Synthesis Example 9> Synthesis of polytetramethylene glycol-based urethane (meth)acrylate compound UA9 A polytetramethylene glycol-based urethane (meth)acrylate compound UA9 was obtained in the same manner as in Synthesis Example 2, except that 39.1 mmol of diphenylmethane diisocyanate was used as the (b) polyisocyanate compound. The molar ratio (b) / (a) of the (a) polyol compound to the (b) polyisocyanate compound in the obtained polytetramethylene glycol-based urethane (meth)acrylate compound UA9 was 0.741.

[0076] [Other components of the acrylic adhesive composition] The components constituting the acrylic adhesive composition other than the polytetramethylene glycol-based urethane (meth)acrylate compounds UA1 to UA9 are as follows. Polytetramethylene glycol-based urethane (meth)acrylate compound UA10 A commercially available product obtained by reacting (a) polytetramethylene glycol having a molecular weight of 650 as a polyol compound with (b) hydrogenated diphenylmethane diisocyanate as a polyisocyanate compound such that the molar ratio (b) / (a) of (a) polyol compound to (b) polyisocyanate compound is 2.0, and (c) using 2-hydroxyethyl acrylate as a terminal (meth)acrylate agent.

[0077] Polytetramethylene glycol (Hodogaya Chemical Co., Ltd., PTG-2900SN) Acryloylmorpholine (KJ Chemicals, ACMO) Isobornyl methacrylate (Kyoeisha Chemical Co., Ltd., Light Ester IB-X) Methacrylic acid (Mitsubishi Chemical Corporation, methacrylic acid) Methyl methacrylate (Mitsubishi Chemical, MMA) 2-Hydroxypropyl methacrylate (Kyoeisha Chemical Co., Ltd., Light Ester HOP) 2-Hydroxyethyl methacrylate (Kyoeisha Chemical Co., Ltd., Light Ester EH) Methacrylic acid 2-ethyl acid phosphate (Kyoeisha Chemical Co., Ltd., Light Ester P-1M, phosphate group-containing methacrylic monomer) Dicyclopentanyl methacrylate (Resonac Corporation, Fancryl FA-513M) Tetrahydrofurfuryl acrylate (Kyoeisha Chemical Co., Ltd., Light Acrylate THF-A) Light Ester 1,6HX (Kyoeisha Chemical Co., Ltd., 1,6-hexanediol dimethacrylate) Light Ester BP-2EM (manufactured by Kyoeisha Chemical Co., Ltd., EO adduct of bisphenol A dimethacrylate)

[0078] ·CHP (NOF Corporation, Percumyl H80, cumene hydroperoxide) Kane Ace M521 (Kaneka Corporation, MBS resin core-shell polymer) Paraffin wax 115 (waxy wax, manufactured by Nippon Seiro Co., Ltd.) Paraffin wax 125 (waxy wax, manufactured by Nippon Seiro Co., Ltd.) EDTA (Chilest Co., Ltd., Chelest 400, ethylenediaminetetraacetate sodium (sodium tetrahydrate) ·Naseem Vanadyl (Nihon Kagaku Sangyo Co., Ltd., vanadyl acetylacetone complex) Malic acid (Tokyo Chemical Industry Co., Ltd., reagent) Benzoquinone (Tokyo Chemical Industry Co., Ltd., reagent) Hydroquinone (Tokyo Chemical Industry Co., Ltd., reagent) AO-60 (ADEKA, hindered phenol antioxidant) Super Ester 100 (special rosin ester, manufactured by Arakawa Chemical Industries Co., Ltd.) Saccharin (Tokyo Chemical Industry Co., Ltd., reagent, o-sulfobenzimide) Acetylphenylhydrazine (manufactured by Sanuki Chemical Industry Co., Ltd.) Copper neodecanoate (5% copper solution, manufactured by Nippon Chemical Industries Co., Ltd.)

[0079] [Example 1] The following raw materials were used to prepare a two-liquid mixed acrylic adhesive: (A) component A and B both contained 30 parts by weight of polytetramethylene glycol urethane (meth)acrylate compound UA1, (B) component A and B both contained 40 parts by weight of isobornyl methacrylate, 10 parts by weight of 2-hydroxypropyl methacrylate, 18 parts by weight of methacrylic acid, and 1.5 parts by weight of 2-ethyl methacrylic acid phosphate, and both A and B both contained 12 parts by weight of Kane Ace M521, 1 part by weight of paraffin wax 115, and 0.04 parts by weight of hydroquinone as a stabilizer. As component (C), 0.8 parts by weight of CHP (cumene hydroperoxide) was used in agent A, and as component (D), 0.35 parts by weight of nursem vanadyl was used in agent B. As other additives, 0.1 parts by weight of EDTA, 0.1 parts by weight of malic acid, and 0.03 parts by weight of benzoquinone were used in agent A, and 0.1 parts by weight of AO-60 was used in agent B. The raw materials were thoroughly mixed and stirred to prepare two-part mixed acrylic adhesives, parts A and B. Kane Ace M521 and Paraffin Wax 115 were dissolved and mixed while heating to around 60-80°C. The viscosity of the resulting adhesive was measured using a Brookfield viscometer, finding that part A was 4.9 Pa s and part B was 5.1 Pa s. A two-part cartridge was filled with component A and component B in a 1:1 ratio, and the components were mixed using a static mixer at the tip of the cartridge while being discharged. The adhesive was used to measure the tensile shear adhesive strength and T-peel adhesive strength. The results are shown in Table 1.

[0080] [Examples 2 to 5] A two-liquid mixed acrylic adhesive was prepared in the same manner as in Example 1, except that UA2 to 5 listed in Table 1 were used as component (A), 0.4 parts by weight of CHP as component (C), and 0.5 parts by weight of Paraffin Wax 125 instead of Paraffin Wax 115 as an additive were used, and the viscosity of agent B was measured using a parallel plate type rotational viscometer to determine the relative value to agent B of Example 1. Using the prepared agents A and B, the tensile shear adhesive strength and T-peel adhesive strength were measured in the same manner as in Example 1. The results are shown in Table 1.

[0081] [Example 6] A two-part mixed acrylic adhesive was prepared in the same manner as in Example 2, except that UA6 was used as component (A) and paraffin wax was not used, and the viscosity of agent B was measured. Using the prepared agents A and B, the tensile shear adhesive strength and T-peel adhesive strength were measured in the same manner as in Example 1. The results are shown in Table 1.

[0082] [Comparative Example 1] A two-part mixed acrylic adhesive was prepared in the same manner as in Example 2, except that UA10 and 0.3 parts by weight of Paraffin Wax 125 were used as component (A), and the viscosity of agent B was measured. Using the prepared agents A and B, the tensile shear adhesive strength and T-peel adhesive strength were measured in the same manner as in Example 1. The results are shown in Table 1.

[0083] [Comparative Examples 2 to 4] A two-part mixed acrylic adhesive was prepared in the same manner as in Example 2, except that UA7 to 9 listed in Table 1 were used as component (A), and the viscosity of agent B was measured. Using the prepared agents A and B, the tensile shear adhesive strength and T-peel adhesive strength were measured in the same manner as in Example 1. The results are shown in Table 1.

[0084] [Comparative Example 5] A two-part mixed acrylic adhesive was prepared in the same manner as in Example 2, except that polytetramethylene glycol without a (meth)acrylate group at the end was used as component (A), and the viscosity of agent B was measured. Using the prepared agents A and B, the tensile shear adhesive strength and T-peel adhesive strength were measured in the same manner as in Example 1. The relative viscosity was 65, and the tensile shear adhesive strength was 8.6 N / mm 2 The T-peel adhesive strength was 0.4 N / mm.

[0085] [Table 1]

[0086] As is clear from Examples 1 to 6, the acrylic adhesive of the present invention, in which the molar ratio (b) / (a) of the (a) polyol compound to the (b) polyisocyanate compound in the polytetramethylene glycol urethane (meth)acrylate compound used is between 0 and 0.5, is an acrylic adhesive that has low viscosity, excellent workability, and exhibits high peel strength and shear strength. On the other hand, in Comparative Example 1, in which the molar ratio (b) / (a) of the (a) polyol compound to the (b) polyisocyanate compound in the polytetramethylene glycol urethane (meth)acrylate compound used is 2.0, it exhibits high shear strength at low viscosity, but the peel strength is extremely low.

[0087] In Comparative Examples 2 to 4, in which the molar ratio (b) / (a) of (a) polyol compound to (b) polyisocyanate compound in the polytetramethylene glycol-based urethane (meth)acrylate compound used was greater than 0.5 and less than 1.0, high peel strength and shear strength were exhibited, but the viscosity was extremely high, resulting in poor workability. In addition, in Comparative Example 5, in which polytetramethylene glycol not having a (meth)acrylate group at the end was used, even though (b) / (a) was 0, the viscosity was low, but the peel strength and shear strength were significantly low.

[0088] [Example 7] Except for using 15 parts by weight of UA1 as component (A), components A and B were prepared in the same manner as in Example 2, and the relative viscosity, tensile shear adhesive strength, and T-peel adhesive strength were measured. The relative viscosity was 57, and the tensile shear adhesive strength was 29.8 N / mm 2 The T-peel adhesive strength was 4.4 N / mm.

[0089] [Example 8] Agents A and B were prepared in the same manner as in Example 2, except that 60 parts by weight of UA1 was used as component (A), and the relative viscosity, tensile shear adhesive strength, and T-peel adhesive strength were measured. The relative viscosity was 247, and the tensile shear adhesive strength was 24.1 N / mm 2 The T-peel adhesive strength was 9.8 N / mm.

[0090] [Example 9] A two-part mixed acrylic adhesive was prepared in the same manner as in Example 1, except that 18 parts by weight of Kane Ace M521 was used as an additive in both Agent A and Agent B. The viscosity of Agent B was measured, and the relative viscosity value was 199. Using the prepared Agent A / Part B, the tensile shear adhesive strength and T-peel adhesive strength were measured in the same manner as in Example 1. The tensile shear adhesive strength was 30.2 N / mm 2 The T-peel adhesive strength was 10.2 N / mm.

[0091] [Example 10] As the (A) component, both Agent A and Agent B used 30 parts by weight of polytetramethylene glycol-based urethane (meth)acrylate compound UA1, as the (B) component, both Agent A and Agent B used 50 parts by weight of methyl methacrylate, 18 parts by weight of methacrylic acid, and 1.5 parts by weight of methacrylic acid 2-ethyl acid phosphate, as well as 12 parts by weight of Kane Ace M521 as an additive, both Agent A and Agent B used 0.4 parts by weight of CHP (cumene hydroperoxide) as the (C) component, and as the (D) component, 0.35 parts by weight of nursem vanadyl as the (D) component. The raw materials were thoroughly mixed and stirred to prepare two-part mixed acrylic adhesives, Part A and Part B. Kane Ace was dissolved and mixed while heating to about 60°C. The viscosity of agent B was measured, and the relative viscosity value was 44. Using the prepared agent A / agent B, the tensile shear adhesive strength and T-peel adhesive strength were measured in the same manner as in Example 1. The tensile shear adhesive strength was 29.5 N / mm 2 The T-peel adhesive strength was 10.8 N / mm.

[0092] [Example 11] Agents A and B were prepared in the same manner as in Example 7, except that the (A) component was 40 parts by weight of polytetramethylene glycol-based urethane (meth)acrylate compound UA1 for both agents, the (B) component was 30 parts by weight of methyl methacrylate, 10 parts by weight of hydroxypropyl methacrylate, 5 parts by weight of acryloylmorpholine, 13 parts by weight of methacrylic acid, and 1.5 parts by weight of 2-ethyl methacrylic acid phosphate for both agents, and 6 parts by weight of Kane Ace M521 was used as an additive for both agents A and B. The viscosity relative value, tensile shear adhesive strength, and T-peel adhesive strength were measured. The viscosity relative value was 84, and the tensile shear adhesive strength was 24.3 N / mm 2 The T-peel adhesive strength was 9.9 N / mm.

[0093] [Example 12] Agents A and B were prepared in the same manner as in Example 7, except that as component (A), 20 parts by weight of polytetramethylene glycol-based urethane (meth)acrylate compound UA1 was used for both agents, and as component (B), 40 parts by weight of methyl methacrylate, 20 parts by weight of isobornyl methacrylate, 10 parts by weight of hydroxypropyl methacrylate, 18 parts by weight of methacrylic acid, and 1.5 parts by weight of 2-ethyl methacrylic acid phosphate were used for both agents. The viscosity relative value was 15, and the tensile shear adhesive strength and T-peel adhesive strength were measured. The viscosity relative value was 15, and the tensile shear adhesive strength was 34.3 N / mm 2 The T-peel adhesive strength was 11.1 N / mm.

[0094] [Example 13] Agents A and B were prepared in the same manner as in Comparative Example 1, except that UA1 was used for both agents as component (A), methacrylic acid 2-ethyl acid phosphate (B) was not added to agent B but was added in 3 parts by weight only to agent A, 4 parts by weight of CHP (C) was used in agent A, and 2 parts by weight of ethylenethiourea (D) was used in agent B. The viscosity relative value was 92, and the tensile shear adhesive strength and T-peel adhesive strength were measured. The viscosity relative value was 92, and the tensile shear adhesive strength was 10.7 N / mm 2 The T-peel adhesive strength was 7.8 N / mm.

[0095] [Example 14] A two-part mixed acrylic adhesive was prepared in the same manner as in Example 2, except that UA1 was used as component (A) and 20 parts by weight of rosin ester (Super Ester 100) was added as an additive. The viscosity of agent B was measured, and the relative viscosity value was 129. The tensile shear adhesive strength and T-peel adhesive strength were measured in the same manner as in Example 1 using the prepared agents A and B. The tensile shear adhesive strength was 28.4 N / mm 2 The T-peel adhesive strength was 9.7 N / mm.

[0096] [Example 15] A two-part mixed acrylic adhesive was prepared in the same manner as in Example 1, except that 6 parts by weight of Kane Ace M521 was used as an additive in both Agent A and Agent B. The viscosity of Agent B was measured, and the relative viscosity value was 34. The tensile shear adhesive strength and T-peel adhesive strength were measured in the same manner as in Example 1 using the prepared Agent A / Part B. The tensile shear adhesive strength was 31.0 N / mm 2 The T-peel adhesive strength was 10.3 N / mm.

[0097] [Example 16] Agents A and B were prepared in the same manner as in Comparative Example 1, except that UA1 was used as component (A) for both agents A and B, and 40 parts by weight of isobornyl methacrylate, 10 parts by weight of 2-hydroxypropyl methacrylate, 10 parts by weight of hydroxyethyl methacrylate, 5 parts by weight of Light Ester BP-2EM, 5 parts by weight of Light Ester 1,6HX, 10 parts by weight of dicyclopentanyl methacrylate, 5 parts by weight of tetrahydrofurfuryl acrylate, 18 parts by weight of methacrylic acid, and 1.5 parts by weight of 2-ethyl methacrylate acid phosphate were used as components (B). The viscosity relative value was 32, and the tensile shear adhesive strength and T-peel adhesive strength were measured. The viscosity relative value was 32, and the tensile shear adhesive strength was 30.6 N / mm 2 The T-peel adhesive strength was 4.2 N / mm.

[0098] [Example 17] The A agent was prepared with the following composition. As the (A) component, 30 parts by weight of polytetramethylene glycol urethane (meth)acrylate compound UA1 was used, as the (B) component, 40 parts by weight of isobornyl methacrylate, 10 parts by weight of 2-hydroxypropyl methacrylate, 18 parts by weight of methacrylic acid, 1.5 parts by weight of 2-ethyl methacrylic acid phosphate, 12 parts by weight of Kaneace M521 as an additive, 0.04 parts by weight of hydroquinone, 0.63 parts by weight of saccharin, 0.32 parts by weight of acetylphenylhydrazine as a stabilizer, and 0.4 parts by weight of CHP as the (C) component. As the (D) component, nursem vanadyl was dissolved in ethanol so that vanadium was 0.5% by weight, and prepared as the B agent. The viscosity of agent A was measured using a parallel plate type rotational viscometer to determine the relative viscosity value. Agent B was applied thinly as a primer to one side of an SPCC steel plate, the solvent was then dried, and agent A was applied to another SPCC steel plate. The two plates were then bonded together while adjusting the thickness of the adhesive layer, and after curing, the tensile shear adhesive strength and T-peel adhesive strength were measured. The relative viscosity value was 104, and the tensile shear adhesive strength was 21.4 N / mm 2 The T-peel adhesive strength was 5.6 N / mm.

[0099] [Example 18] Agents A and B were prepared in the same manner as in Example 17, except that 4 parts by weight of CHP was used as component (C), and the relative viscosity, tensile shear adhesive strength, and T-peel adhesive strength were measured. The relative viscosity was 87, and the tensile shear adhesive strength was 17.4 N / mm 2 The T-peel adhesive strength was 5.3 N / mm.

[0100] [Example 19] Agents A and B were prepared in the same manner as in Example 17, except that, as component (D), instead of nursem vanadyl, a 5% solution of copper neodecanoate was further diluted with ethanol so that the copper content was 0.5% by weight to prepare Agent B. Test specimens were prepared in the same manner as in Example 17, except that the SPCC steel plates were attached to each other without removing the thickness of the adhesive layer, and the tensile shear adhesive strength and T-peel adhesive strength were measured. The tensile shear adhesive strength was 24.8 N / mm 2The T-peel adhesive strength was 4.6 N / mm.

Claims

1. (A) a polytetramethylene glycol-based urethane (meth)acrylate compound having a (meth)acrylate group at its terminal, a polytetramethylene glycol-based urethane (meth)acrylate compound obtained by reacting a polytetramethylene glycol-based prepolymer obtained by reacting (a) a polyol compound with (b) a polyisocyanate compound in a molar ratio of (b) component / (a) component in the range of 0 to 0.5, with (c) a terminal (meth)acrylate agent; (B) a polymerizable vinyl monomer, (C) organic peroxide, (D) a reducing agent, An acrylic adhesive composition comprising as an essential component:

2. 2. The acrylic adhesive composition according to claim 1, wherein, when the total amount of the component (A) and the component (B) is 100 parts by weight, the component (A) is 5 to 60 parts by weight, the component (B) is 40 to 95 parts by weight, the component (C) is 0.05 to 10 parts by weight, and the component (D) is 0.01 to 10 parts by weight.

3. The (b) polyisocyanate compound is selected from the following (i) to (iv): (i) an aliphatic polyisocyanate compound, (ii) alicyclic polyisocyanate compounds, (iii) a biuret, nurate, adduct, allophanate, carbodiimide or polymer of an aliphatic polyisocyanate compound; (iv) a biuret, a nurate, an adduct, an allophanate, a carbodiimide or a polymer of an alicyclic polyisocyanate compound; The acrylic adhesive composition according to claim 1 or 2, which is one or more selected from the group consisting of:

4. The acrylic adhesive composition according to claim 1 or 2, wherein the (c) terminal (meth)acrylate agent is an isocyanate group-containing (meth)acrylate compound or a carboxyl group-containing (meth)acrylate compound.

5. The acrylic adhesive composition according to claim 1 or 2, wherein the (B) polymerizable vinyl monomer comprises a (meth)acryloyl-based monomer having one or more (meth)acryloyl groups.

6. The acrylic adhesive composition according to claim 1 or 2, wherein the (B) polymerizable vinyl monomer comprises methacrylic acid.

7. The acrylic adhesive composition according to claim 1 or 2, wherein the (B) polymerizable vinyl monomer comprises a (meth)acrylic acid ester containing a phosphate ester group.

8. The acrylic adhesive composition according to claim 1 or 2, further comprising (E) a core-shell rubber.

9. A cured product of the acrylic adhesive composition according to claim 1 or 2.

10. A product having the cured product according to claim 9 as a component.

Citation Information

Patent Citations

  • Adhesive set and method of manufacturing structure

    JP2020041042A

  • Compositions based on methacrylate monomers

    JP2022526354A

  • Composition

    WO2020100832A1

  • Heat-resistant acrylic adhesive composition

    WO2022249965A1

Cited By

  • Method for producing steel sheet laminate, steel sheet laminate, and adhesive composition

    WO2026197167A1